FAKTOR-FAKTOR YANG MEMENGARUHI KEPUTUSAN MAHASISWA MEMILIH UNIVERSITAS NAHDLATUL ULAMA PURWOKERTO - Herdian Farisi; Anjar Safitri (Faculty of Social, Economics and Humanities, 2022)
The aim is to determine the factors that influence students' decisions to choose Universitas Nahdlatul Ulama Purwokerto and the most dominant factors for students to choose Universitas Nahdlatul Ulama Purwokerto. This study uses an exploratory factor analysis method with the variables studied, namely from internal factors including Motivation, Attitudes, Perceptions, Learning, and external factors including Marketing Mix, Service Quality, Reference Group, and Social Level. The sample used is the student population of Universitas Nahdlatul Ulama Purwokerto Batch 2018 and 2019. The results of the most dominant factor analysis are the Attitude variable with popular indicators, Perception with lecturer competency indicators, Marketing Mix with SPP indicators and the availability of curriculum or study programs of interest, and Quality of Service easily interacts with lecturers or teaching staff.